The Impact of Fiscal Policy on Welfare Improvement in Indonesia: Study of Impact of Premium Assistance Beneficiaries on The National Health Insurance, Physical Special Allocation Fund for Health Sector, Education Sector, and Village Funds to Human Development Index - Ahmad Nawawi; Wihana Kirana Jaya; Mulyadi Sumanto; Evita Hanie Pangaribowo (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2021)
One of the objectives of the fiscal policy is to improve public welfare. Still, there are funding constraints to improve welfare in some countries. Therefore, fiscal management to increase welfare must be implemented efficiently and effectively. In this research, to improve welfare, the fiscal policy will be focused on health, education and community empowerment which are the components of the HDI. This research used quantitative method with regression equation to explain the impact of fiscal and social policy, in the form of Recipients of Health Insurance Contribution Assistance (Penerima Bantuan Iuran Jaminan Kesehatan Nasional/ PBI JKN), physical special allocation found (Dana Alokasi Khusus/DAK) for health and education sector, village fund, region’s budget expenditure, locally generated revenue (Pendapatan Asli Daerah/PAD), and poverty level on human development index (HDI) improvement. The locus for this research is all regencies/cities in Indonesia that use panel data. The results of this research were divided into three findings. First, there were research variables with unidirectional results and significant improvement on HDI, which are physical DAK for the health and education sector, village funds, social expenditure, and PAD. Second, there were variables with unidirectional impact but it does not have a significant impact on the HDI improvement (i.e. PBI JKN). Third, there were variables with unidirectional and significant impact, such as personnel expenditure, material expenditure, capital expenditure, and poverty level.